Cancer registration and information systems in Latin America - Arrossi, Silvina (2015)
In 2011, only 21% of countries in Latin America had a population-based cancer registry. As a result, accurate estimations of cancer burden and risks faced by diff erent countries and populations were not possible. The 2013 Lancet Oncology Commission1 on cancer control in Latin America and the Caribbean showed the shortage of local scientifi c evidence and economic data regarding cancer prevention and control. Moreover, the authors reported that cancer control programmes faced structural problems of inadequate funding; inequitable distribution of resources and services, and no adequate care for many populations based on socioeconomic, geographical, and ethnic factors. Accurate, updated, and comparable data are essential to measure eff ectiveness of health programmes, so in the absence of a real priority assigned to cancer control, the dearth of development of cancer registries is unsurprising. Thus, the problem of cancer registration can be thought of as the tip of the iceberg for insuffi cient eff ective cancer control programmes.